2023
DOI: 10.1101/2023.01.07.23284294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building case investigation and contact tracing programs in U.S. state and local health departments: a conceptual framework

Abstract: The COVID-19 pandemic and earlier health events have demonstrated that when effectively implemented, case investigation and contact tracing (CI/CT) can break chains of transmission by promptly identifying, quarantining, and monitoring the contacts of infected cases, thereby limiting further spread of a disease in a community. Many public health experts agree that implementing CI/CT at the early stages of an outbreak can be an extremely effective approach to controlling an outbreak; as such, health departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Frontline staff identi ed preemptively sta ng for surges as an area of improvement. Our ndings reinforce lessons gathered from a narrative literature review and qualitative interviews with US state and local health department o cials and public health experts [10] -case investigation and contact tracing programs need to be able to pivot their goals and practices as an outbreak evolves, including updating procedures, training materials, call scripts, and data systems, and scaling up the workforce as needed.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Frontline staff identi ed preemptively sta ng for surges as an area of improvement. Our ndings reinforce lessons gathered from a narrative literature review and qualitative interviews with US state and local health department o cials and public health experts [10] -case investigation and contact tracing programs need to be able to pivot their goals and practices as an outbreak evolves, including updating procedures, training materials, call scripts, and data systems, and scaling up the workforce as needed.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies published regarding other COVID-19 contact tracing programs emphasized the importance of public health programs recruiting staff from communities that they seek to serve [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research described a narrative literature review to identify the capacities of CI/CT programs. 5 Capacities were bucketed into 3 broad domains—organizational, technical, and social—based on the nature of their function. Once this CI/CT capacity framework was developed, we conducted qualitative interviews between May and August 2022 with officials at US state and local health agencies and public health experts in federal agencies and public health organizations.…”
Section: Methodsmentioning
confidence: 99%
“…To address the lack of comprehensive guidelines describing the capacities and capabilities of CI/CT programs, our earlier research identified and described the relationships between these capacities and capabilities. 5 Capacities refer to the organizational, technical, and social resources (eg, governance, workforce, technology) that are needed to support a CI/CT program's capabilities. Capabilities are aligned with the goals of a CI/CT program and describe what the program is able to accomplish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation